Faktor-Faktor Yang Memengaruhi Trust Dalam Rekomendasi Collaborative Filltering Facebook Terhadap Purchase Intentions - Gerardus Ananta Banyu; Heddry Purba (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Social recommendation systems have gained increasing popularity. This study seeks to understand the influence of factors that influence trust on purchase intention in social recommendation systems. The method used is a correlational model using an online questionnaire and distributed to 201 Facebook Marketplace users. The findings validate that recommendation persuasiveness strongly predicts trust in recommendation, while perceived risk is inversely related to trust in recommendation. The authors underscore that Trust in Recommendation significantly shapes purchase intentions, highlighting the importance of recommendations and consumers' perception of associated Perceived Risk, both of which influence consumer attitudes. This research illustrates that consumers' trust in recommendations fully mediates the factors that influence their Purchase Intention. Keywords: Perceived Risk, Social Recommender System, Trust in Recommendation, Purchase Intention, Recommendation Persuasiveness